2007
DOI: 10.1038/sj.ejhg.5201932
|View full text |Cite
|
Sign up to set email alerts
|

8p23.1 duplication syndrome; a novel genomic condition with unexpected complexity revealed by array CGH

Abstract: The 8p23.1 deletion syndrome is established but not an equivalent duplication syndrome. Here, we report five patients; a de novo prenatal case and two families in which 8p23.1 duplications have been directly transmitted from mothers to children. Dual-colour fluorescent in situ hybridisation, multiplex ligation-dependent probe amplification analysis and customised oligonucleotide array comparative genomic hybridisation (oaCGH) indicated an approximately 3.75 Mb duplication of most of band 8p23.1 between the olf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 30 publications
3
78
1
3
Order By: Relevance
“…On the basis of the finding of three probands with 8p23.1 duplication in this study, or a 0.31% detection rate, we suspect that the 8p23.1 duplication may be more common than previously suspected. 7 Rare genomic abnormalities reveal the possible existence of multiple hotspots leading to variable genomic rearrangements on 8p The specific genomic abnormalities of patients 1 and 7-10 in this study have not been previously reported. However, these rare genomic abnormalities reveal the occurrence of several unstable regions leading to recurrent genomic rearrangements on 8p.…”
Section: P231 Duplicationmentioning
confidence: 61%
See 4 more Smart Citations
“…On the basis of the finding of three probands with 8p23.1 duplication in this study, or a 0.31% detection rate, we suspect that the 8p23.1 duplication may be more common than previously suspected. 7 Rare genomic abnormalities reveal the possible existence of multiple hotspots leading to variable genomic rearrangements on 8p The specific genomic abnormalities of patients 1 and 7-10 in this study have not been previously reported. However, these rare genomic abnormalities reveal the occurrence of several unstable regions leading to recurrent genomic rearrangements on 8p.…”
Section: P231 Duplicationmentioning
confidence: 61%
“…7,42 Three probands (patients 4-6) in this study were observed to have the 8p23.1 duplication (Table 1; Figure 1; Supplementary Figure S1b). The 8p23.1 duplication in patient 4 was inherited from the affected mother.…”
Section: P231 Duplicationmentioning
confidence: 71%
See 3 more Smart Citations